Ischemic Toes after Venous Thromboembolism: A Difficult Differential Diagnosis with Good Response to Combination Therapy—A Case Report - Mohammad Bagher Owlia; Ahmad Salimzadeh; Gholmhossein Alishiri; Saeed Kargar (Case Reports in Medicine)
The obliteration of the arterial vascular system of toes is considered as a potentially catastrophic event in clinical practices. In most instances, the cessation of arterial blood flow heralds a serious underlying pathology. A definite classification of some cases is somehow difficult and subject to diagnostic challenges. The aim of the present case study is to share and discuss potentially complex and multifactorial mechanisms of some acute vascular events. In this report, we deal with a 46-year-old man with a rather gradual-onset ischemia of his toe who responded favorably to a combination of pulsed glucocorticoid and anticoagulation within a week.